Polychlorinated biphenyls and organochlorine pesticides in European eel (Anguilla anguilla) from the Garigliano River (Campania region, Italy) - FERRANTE, MARIA CARMELA; MELI, ROSARIA; Clausi M. T.; Fusco G.; Naccari C.; Lucisano A. (Chemosphere, 2010)
Measuring organochlorine compounds in muscle tissue of European eels from the Garigliano River in Campania (Italy), overall PCBs emerged as the most abundant pollutants, followed by DDTs, Dieldrin and HCB. Target PCBs, IUPAC nos. 118, 138, 153 and 180, were the dominant congeners accounting for 64.2% of total PCBs. Among OCPs, p,p'-DDE was detected in all eels, always with higher concentration levels than other OCPs; p,p'-DDT was frequently detected, about 93.3% of the sample. The high and statistically significant correlations between concentration and length as well as weight of eels suggest that the organochlorine compounds concentrations tend to increase with the size and consequently with the age. Concentrations of DDTs and PCBs detected were similar to those reported in studies relative to France, UK and Sweden. As regards toxicological risk for human health, in general OCPs residual levels were below the limits established for fish and aquatic products. Conversely, the concentrations of PCBs exceeded the limit set by the EU for terrestrial foods. Our results imply that OCPs and PCBs are still important persistent chemical contaminants in Campania freshwaters, although their manufacture and use are banned or highly restricted.